2018
DOI: 10.1142/9789813239913_0010
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Research, Technology and Nutrition in Sub-Saharan Africa

Abstract: The objective of this study is to examine the relationships between agricultural research, technology and nutrition in Sub-Saharan Africa (SSA), drawing upon a rich and insightful literature. African agriculture has the lowest productivity compared with other regions of the world. Huge productivity gains are possible and accrue where governments allocate the necessary resources to agricultural research and development. In SSA, however, public investment in agriculture is still far lower than needed. Food and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A few authors concluded that digital solutions could address a wide range of gaps and inefficiencies in AVCs such as information sharing and analytics, access to markets, access to finance as well as tracking and traceability (El Bilali & Allahyari, 2018;FAO, 2013;FAO & ITU, 2017;GSMA, 2018;OECD, 2019). Returns on agricultural research and digital technology involve impact on crop and livestock, economic growth, natural resource management, nutrition, poverty reduction, and food security (Gaiha & Mathur, 2018). The Connected Farmer Alliance (CFA) creates solutions to supply chain efficiencies, linking farmers to commercial markets while facilitating productivity improvements (OECD, 2019).…”
Section: Economic Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…A few authors concluded that digital solutions could address a wide range of gaps and inefficiencies in AVCs such as information sharing and analytics, access to markets, access to finance as well as tracking and traceability (El Bilali & Allahyari, 2018;FAO, 2013;FAO & ITU, 2017;GSMA, 2018;OECD, 2019). Returns on agricultural research and digital technology involve impact on crop and livestock, economic growth, natural resource management, nutrition, poverty reduction, and food security (Gaiha & Mathur, 2018). The Connected Farmer Alliance (CFA) creates solutions to supply chain efficiencies, linking farmers to commercial markets while facilitating productivity improvements (OECD, 2019).…”
Section: Economic Categorymentioning
confidence: 99%
“…. (2016),Bayer (2018),Boateng et al (2017),Bukht and Heeks (2018),Constantinides et al (2018),Corallo et al (2018),Deichmann and Mishra (2019),Deichmann et al (2016), El Bilali andAllahyari (2018),Foster and Heeks (2015),Gaiha and Mathur (2018),Gillespie et al (2007), GSMA (2018),Habiyaremye et al (2019),Heeks (2018),Heeks (2016),Mattern and Ramirez (2017), OECD (2019), Paudel et al (2020) Reports/grey literature 8 Begashaw et al (2019), EIP-AGRI (2017), FAO and AUC (2018), FAO, et al (2018), Jackson and Weinberg (2016), Juma (2019), Odini (2014), UN (2019) Webpages 9 FAO (2013),Graham (2019), ITU (2016),Lee et al (2017),Malan (2018),Maru et al (2018),Rose and Chilvers (2018), Thamaga-Chitja and Morojele (2014),Tuli (2005) …”
mentioning
confidence: 99%
“…With the availability of credit, sorghum agriprenuers have a better capacity to invest in various innovations. Credit also enables agriprenuers to purchase farm inputs improved sorghum seeds, agrochemicals, hire extra labour hence improve the farm's competitiveness (Gaiha & Mathur, 2019).…”
Section: Institutional Characteristics Of Sorghum Agriprenuersmentioning
confidence: 99%
“…The continuous rise in the population also means that there will be food insecurity due to inadequate food supply. According to Raghav and Shantanu (2018), the demand for food will rise with the rise in the population, which implies that there will be a need to increase food production to curb this situation. There is a need for the government to also curb the population increase through educations such as family planning and controlled population.…”
Section: Food Security Regarding Supply and Demandmentioning
confidence: 99%
“…Those living in rural areas are still naï ve with such things, and as such, they give birth to more children than they can feed. High population means that there will be high food demands, which will consequently lead to an increase in the possibility of food insecurity (Raghav & Shantanu, 2018). The government, through relevant ministries, should plan on how it can create equilibrium in this situation by putting in place mechanisms that will help in increasing food supply.…”
Section: Food Security Regarding Supply and Demandmentioning
confidence: 99%